1961
DOI: 10.1152/ajplegacy.1961.201.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of carotid occlusion response by anesthesia

Abstract: Dogs under chloralose anesthesia show augmented reflex responses of systolic arterial pressure, mean arterial pressure, diastolic arterial pressure, and pulse rate to bilateral occlusion of the common carotid arteries over the responses of these same parameters before any anesthesia. Hyporeflexia, as indicated by these parameters, is observed when the anesthetic is chloralose and urethan, pentobarbital, or thiobarbital. Less variance in the responses as a result of alteration of the anesthetic level is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Consistent with these findings is the report by Armstrong, Porter & Langston (1961), that the pressor response to carotid occlusion in conscious dogs was augmented by chloralose and depressed by urethane and barbiturates. Although the cause of these changes is not known, the present experiments suggest an effect of the anaesthetic on cardiovascular responsiveness to sympathetic stimulation rather than an effect on the neural pathways of the baroreceptor mechanism.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with these findings is the report by Armstrong, Porter & Langston (1961), that the pressor response to carotid occlusion in conscious dogs was augmented by chloralose and depressed by urethane and barbiturates. Although the cause of these changes is not known, the present experiments suggest an effect of the anaesthetic on cardiovascular responsiveness to sympathetic stimulation rather than an effect on the neural pathways of the baroreceptor mechanism.…”
Section: Discussionsupporting
confidence: 88%
“…However, the peak mean arterial pressure increase and the peak heart-rate decrease were greater before chloralose than before pentobarbitone Na. These results suggest that baroreceptors may be overactive under chloralose anaesthesia (Brown & Hilton, 1956;Armstrong, Porter & Langston, 1961) and underactive under pentobarbitone Na anaesthesia (Cox, 1972a). Cox (1972a) noticed that pentobarbitone Na reduced the increase in heart rate and output caused by isoprenaline.…”
Section: Discussionmentioning
confidence: 97%
“…Armstrong et al (27) reported a lower heart rate. Cardiac output has been reported to range from an increase with (1 9) or without (25, 26) tachycardia, variable changes over time (1 1, 18), a decrease (18,21), and no effect (7).…”
Section: Pulmonary Vascular Resistancementioning
confidence: 95%
“…Study conditions have ranged from mechanical (7, 18, 19,2 1-23,28) to spontaneous ventilation (1 1, 20, 24-27) and from acute (18,19,28) to chronic instrumentation (7, l l , [20][21][22][23][24][25][26][27]. Moreover, studies have used different doses of chloralose, various supplemental solvents or anesthetic agents, and different species and ages of animals.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 99%